Acute Decompensated Heart Failure: Evolving Literature and Implications for Future Practice. Issue 4 (11th November 2013) - Cicci, Jonathan D.; Reed, Brent N.; McNeely, Elizabeth B.; Oni‐Orisan, Akinyemi; Patterson, J. Herbert; Rodgers, Jo E.
<x xml:space="preserve">Abstract</x> Acute decompensated heart failure (ADHF) is associated with substantial morbidity and mortality, and represents a considerable financial burden to society. Historically, few prospective, randomized, double‐blinded trials have investigated the optimal management of ADHF, and most guideline recommendations are based primarily on expert opinion. However, in the last decade, a considerable amount of research has added to the understanding of the management of ADHF in both patients with fluid overload and low cardiac output. In addition, as mechanical circulatory support devices and heart transplantation continue to evolve, significant advances have also been made with regard to the proper selection of patients for advanced surgical options. Finally, several novel pharmacologic agents have shown promise in early trials and may represent the next steps in ADHF management. Although advances have been made over the past decade, many questions remain.